Efeito do líquido do pseudocaule da bananeira combinado com solução nutritiva na formação de mudas de bananeira. - Severino, Daniely dos Santos Barboza (2011)
The cultivation of banana trees generate lignoselulosic residue by cutting shoots and the plants after bunch collection. The pseudo-stem represents the largest portion of that residue and serves as a medium for the proliferation of pests in banana field. By industrial processing of that fibrous residue is also generated expressive volume of Net’s speudo-stem (LPCB). This study aimed to evaluate the effects LPCB combined with nutrient solution on physiological parameters, shot growth and nutrition of seedlings of the cultivar ‘Prata Anã’. Plantlets were grown on PVC columns of 20 cm diameter by 65 cm high filled with Ultisol from five layers (0-10, 10-20, 20-30, 30-40 and 40-60 cm) and subjected to five dosages of LPCB (0, 288, 576, 864 and 1152 mL, represented by volumetric combinations of water and LPCB (100:0, 75:25, 50:50, 25:75, 0:100, v:v), combined with two concentrations of Hoagland nutrient solution (one strength and half strength), using five replicates for each treatment. After 60 days of plant cultivation the stomata conductance, photosynthetic and chlorophyll contents in leaves were determined and, at the time of harvest, 68 days, were measured plant height and pseudo-stem diameter, counted leaves, determined fresh and dry weight of roots and aerial parts and analyzed N, K and Na contends in roots and aerial parts of banana plants. In layers of soil were evaluated microbiological and chemical characteristics. The results indicated that LPCB affects the dynamics of nutrients in the soil, favoring the accumulation of Na and K in a layer near the surface and reducing the pH in subsurface layers. The LPCB application rates increased microbial biomass and edaphic respiration. A higher dosage of that residue inhibits the plantlet growth and dry weight accumulation. The increasing of LPCB dosages promoted higher photosynthetic rate, but reduces stomata conductance, transpiration and chlorophyll content in leaves of banana plants.